Exploring the Role of Urban Agriculture in Indonesia’s Socio-Economic and Environmental Landscape: A Systematic Literature Review - Aji Saputra; Oekan Soekotjo Abdoellah; Gemilang Lara Utama; Yusep Suparman; Dede Mulyanto; Indri Wulandari (Jurnal Ilmu Lingkungan, 2025)
In the domain of sustainability, urban agriculture is recognized as a key instrument for confronting critical global challenges including but not limited to food security, climate change, and environmental degradation. As an integral component of sustainable practices, urban agriculture offers a comprehensive strategy for addressing these concerns concurrently. The primary aim of this systematic review is to delineate the methodologies implemented for sustainable urban agriculture in Indonesia. Additionally, it assesses the foremost opportunities and challenges in leveraging urban agriculture to achieve environmental, social, and economic objectives. This review used the PRISMA technique to assess 25 articles investigating the relationship between urban agriculture (UA) and sustainability. The studies were selected from the Scopus database, and the aim was to present a comprehensive summary of the current knowledge in this field. Results indicate that urban agriculture offers significant economic, social, and environmental benefits in sustainable urban environments. Realizing its full potential requires coordinated efforts through policy development, community involvement, and overcoming existing obstacles. This study addresses the urgent need for sustainability in cities by integrating farming practices within urban areas, promising food security, reduced environmental impact, and increased urban resilience. With cities facing challenges such as population growth, resource scarcity, and climate change, urban agriculture is key to creating sustainable cities for the future.